2014
DOI: 10.4172/2165-8048.s6-010
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Adipose Tissue and Inflammation in Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) is defined as carbohydrate intolerance with first onset or first identification in pregnancy. It is one of the most common complications of pregnancy with a prevalence ranging from 3% to upwards of 16% depending on the screened population and whether a 1 or 2-step screening algorithm is utilized. Its occurrence has historically been predominantly attributed to pro-diabetogenic placental hormone secretion. However, there is emerging evidence to indicate that its mechanistic u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 106 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…10 For example, AT expandability during pregnancy has been proposed to play a role in the etiology of GDM as supported by gene expression and histological properties of GDM subcutaneous AT. 23,24 According to this view, similarly to what is found in men with metabolic syndrome, 12 decreased ability to store energy in adipocytes plays a role in accentuating IR during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 For example, AT expandability during pregnancy has been proposed to play a role in the etiology of GDM as supported by gene expression and histological properties of GDM subcutaneous AT. 23,24 According to this view, similarly to what is found in men with metabolic syndrome, 12 decreased ability to store energy in adipocytes plays a role in accentuating IR during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Recent research has highlighted the important role of adipose tissue (AT) dysfunction in GDM. 10 AT dysfunction is characterized by excessive lipolysis (adipocyte IR) and inflammation, leading to an increase in adipocyte-derived circulating lipids and cytokines that mechanistically play a role in defective total body insulin-mediated glucose utilization mainly in skeletal muscle. In general IR, including adipocyte IR, is acquired with obesity but not all obese individuals develop adipocyte and systemic IR.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that, insulin resistance and subsequent development of GDM are influenced by adipose tissue (AT) expansion among other factors (Simas and Corvera, 2014;Aziz et al, 2016;Li et al, 2016;Ngala et al, 2017). During pregnancy, AT expands in response to increased fetal growth (Simas and Corvera, 2014) and can expand further due to consumption of a high fat diet (HFD) (Musial et al, 2017). Fetal growth and HFD mediated AT expansion induce insulin resistance during pregnancy and are pivotal to the development of GDM (Aziz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Normally fat storage occurs within SAT, when its storage capacity is exhausted, the fats are stored in ectopic depots around the visceral organs (Smith and Kahn, 2017). The ability of SAT and VAT to accommodate fat storage with hyperplasia rather than hypertrophic expansion may determine the risk for GDM (Simas and Corvera, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation